Efektivitas Media Pembelajaran Canva Terhadap Hasil Belajar Siswa pada Mata Pelajaran Kewirausahaan Kelas XI di SMK Auto Matsuda - Rhamdini, Sita; Haerudin, Dodi Ahmad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the effectiveness of Canva as a learning medium in improving students’ learning outcomes in the subject of Entrepreneurship for grade XI students at SMK Auto Matsuda. The research method used was a quasi-experimental approach with a Nonequivalent Control Group Design. The subjects consisted of 46 students divided into two groups: the experimental class that used Canva as the learning medium and the control class that used conventional methods. Data were collected through observation, pretest and posttest, and documentation. The data were analyzed using descriptive statistics, normality test, homogeneity test, and t-test. The results showed a significant improvement in students’ learning outcomes after using Canva. The average pretest score of the experimental class was 61, which increased to 83 in the posttest, with an average gain of 22 points. The highest score improved from 78 to 100, while the lowest score increased from 45 to 60. The t-test results also indicated a significant difference between the experimental and control groups, proving that Canva is effective in improving students’ learning outcomes. Therefore, Canva can be considered an innovative alternative to support Entrepreneurship learning at vocational high schools, as well as to encourage the implementation of the Merdeka Curriculum, which emphasizes technology integration and student-centered learning.